II. Meşrutiyet Dönemi Türkçenin Sadeleşmesi Tartışmalarında Celal Sahir Erozan - Karaca, Nesrin Tağızade (Kitabevi, 2003)
In this study, Celal Sahir Erozan's involvement as a literary figure in the establishment of the Turkish Language Institution along with Atatürk will be analysed in accordance with "Turkish in Language" which was systematized by Ziya Gökalp in the establishment of the Turkish Republic after the Ottoman Empire. Taking the characteristics of the period into consideration, Celal Sahir Erozan's approach to the movement and his position in the argument of simplifying Turkish will be discussed.
Second Constitution Celal Sahir Erozan's Discussion in Simplifying Turkish Language
Keywords: Second Constitution; Simplifying Turkish; Celal Sahir Erozan; Genç Kalemler